SUKU DUANO DI DESA BELARAS KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Arip, Muhammad; ', Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Duano tribe has similarities with the Malay tribe, namely in terms of physical appearance, way of dressing, traditional customs and religious practices. This form of equality can be said to be a shared inheritance from previous generations. The aspects that are often adapted are in terms of economic, political, socio-cultural activities and marital relations. The identification of the problem in this research is how the social structure of life, social relations, economic relations, of the Duano tribe and other tribes. The aim of this research is to find out the social structure of life, social relations, economic relations, of the Duano tribe and other tribes in the village. Belaras, Mandah District, Indragiri Hilir Regency. In this research, the researcher used a type of research with a descriptive qualitative research method with ethnographic studies. The ethnographic research method is included in the qualitative research group whose characteristics are "researching informants as research subjects in their daily environment. Based on field data, the researcher obtained data on the number of informants in this research, namely five people consisting of one village head, one Duano tribal head (traditional head), as key informants, and supporting informants, one village official, one village resident as additional informant, so that the data obtained from the informants is increasingly strengthened and accurate by the presence of supporting informants. Based on research results, changes in the Duano tribe's economy occurred because of a relationship that existed between the Duano tribe and other tribes who needed each other. then a group is a group, namely a number of people who have a relationship with each other and strata or social stratification is a social phenomenon that cannot possibly be avoided, meaning that it will be found in every society. from the research is that the government always pays attention to life in remote places so that it can always provide assistance to the lives of remote communities. Apart from the government always paying attention to the lives of remote communities, the community itself must have its own way of meeting its daily needs, so that in this way it can be considered as a policy maker. Keywords: Duano Tribe, Economy, Social Relations, Society.